Pretty perfect kitty-corn eaudiobook - Hale, Shannon (Kitty-Corn., 2022)
Unicorn is perfect—everybody thinks so. He yearns to look the way everyone thinks he should. But when a fumble makes Unicorn feel like a big, ugly goof, he can't help but wonder: If he's not absolutely perfect and majestic all the time, will Kitty even want to be his best friend anymore? The magical bestselling team of Shannon Hale and LeUyen Pham put their horns together once again for a heart-bursting story featuring an utterly adorable kitty-corn pair, making it clear that it's okay to embrace our flaws and share the messy parts of ourselves.